Coupling Atomically Dispersed Fe–N5 Sites with Defective N‐Doped Carbon Boosts CO2 Electroreduction. Issue 38 (21st August 2022) - Li, Zhao; Jiang, Jinxia; Liu, Ximeng; Zhu, Zhaozhao; Wang, Junjie; He, Qian; Kong, Qingquan; Niu, Xiaobin; Chen, Jun Song; Wang, John; Wu, Rui
Abstract: Atomically dispersed iron immobilized on nitrogen‐doped carbon catalyst has attracted enormous attention for CO2 electroreduction, but still suffers from low current density and poor selectivity. Herein, atomically dispersed FeN5 active sites supported on defective N‐doped carbon successfully formed by a multistep thermal treatment strategy with the aid of dicyandiamide are reported. This dual‐functional strategy can not only construct intrinsic carbon defects by selectively etching pyridinic‐N and pyrrolic‐N, but also introduces an additional N from the neighboring carbon layer coordinating to the commonly observed FeN4, thus creating an FeN5 active site supported on defective porous carbon nanofibers (FeN5 /DPCF) with a local 3D configuration. The optimized FeN5 /DPCF achieves a high CO Faradaic efficiency (>90%) over a wide potential range of −0.4 to −0.6 V versus RHE with a maximal FECO of 93.1%, a high CO partial current density of 9.4 mA cm −2 at the low overpotential of 490 mV, and a remarkable turnover frequency of 2965 h −1 . Density functional theory calculations reveal that the synergistic effect between the FeN5 sites and carbon defects can enhance electronic localization, thus reducing the energy barrier for the CO2 reduction reaction and suppressing the hydrogen evolution reaction, giving rise to the superior activity and selectivity. Abstract : Atomically dispersed FeN5 active sites supported on defect‐rich porous carbon nanofibers (FeN5 /DPCF) are successfully developed by a two‐step thermal treatment strategy with the aid of dicyandiamide. These active sites promote the activity and selectivity of CO2 electroreduction to CO, showing a high Faradaic efficiency of 93.1% at −0.5 V versus RHE.